The mechanization of manual rotation of shut-off valve electrical drive flywheel in conditions of electric power supply interruption - Brusnik O. V. Oleg Vladimirovich; Paponin I. Yu. Ivan Yurjevich; Miller O. Yu. Oleg Yurjevich; Koloskov R. V. Roman Vladimirovich; Shavlov E. N. Evgeny Nikolaevich (2017, 2017)
Shut-off valve is an important element concerning operation of the main oil pipeline. It has a major role in technical process and elimination of emergency situations. There is a necessity to raise the level of work efficiency of shut-off valve with the purpose of increasing pipeline serviceability. As a rule, electrical drive is used for operation of shut-off valve in oil transportation. According to this we have an urgent problem of electrical drive breakage caused by electric power supply interruption. It is a very common problem in heavy climatic conditions of the far north. Meanwhile, most of oil fields of Russia are located in this area. This article presents the solution of the defined problem. It is suggested to solve it by using the device of a special construction. The principle of its work is considered in this paper. Calculations and selection of optimal parameters of the device for fail-free and safe work are made. The data of the experiment which was carried out on a prototype are presented. The analysis of the research results are shown in the article.